Improvement of physical training of young weightlifters in microcycles at the initial stage - Mavropulo, O. S.; Trufanova, S. N.; Zavodnyi, N. A.; Odintsova, V. I.; Chub, S. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase the efficiency of physical training of young weightlifters in microcycles at the initial stage with the predominant use of the circular training method.